Synergistic Larvicidal and Pupicidal Toxicity and the Morphological Impact of the Dengue Vector (Aedes aegypti) Induced by Geranial and trans-Cinnamaldehyde - Sirawut Sittichok; Hataichanok Passara; Jirisuda Sinthusiri; Tanapoom Moungthipmalai; Cheepchanok Puwanard; Kouhei Murata; Mayura Soonwera (My University, 2024)
Monoterpenes are effective and eco-friendly alternatives to conventional chemical larvicides. We tested single and binary mixtures of monoterpenes-geranial and
Keywords: Insect Pest Control Strategies